Determination of osmotic resistance of erythrocytes using flow cytometry in patients with hereditary spherocytosis - E. F. Mitsura; Zh. N. Pugacheva; L. I. Volkova (Сибирский научный медицинский журнал)
To diagnose hereditary spherocytosis (HS), an osmotic resistance test is used to assess the severity of hemolysis in a series of hypotonic sodium chloride solutions, which demands intensive and time consuming workload and has low sensitivity and specificity. New methods for evaluating osmotic resistance based on flow cytometry were proposed, but they are not sufficiently standardized. Objective: development and testing of the method for determining the osmotic resistance of red blood cells (RBCs) using flow cytometry in patients with HS. Material and methods. In 2017-2019, 33 patients with HS and 30 children in the control group were examined. The method included the study of blood preparations in phosphate-buffered saline (PBS) and their serial dilutions in distilled water using flow cytometry, both in fresh blood and after 24-hour incubation. The proportion of preserved (not hemolized) RBCs was evaluated. As reference intervals, 5 and 95 percentiles of the control group indicators were used. Results and discussion. Among people with HS, before incubation, pathological changes in at least two dilutions were detected in 81.8 % of patients; after incubation, pathological changes were detected additionally in 4 out of 6 patients. Diagnostic sensitivity of the test is 93.9 %, specificity 83.3 %, positive and negative predictive values 86.1 and 92.6 %, respectively. It was found that the method with proposed reference intervals allows evaluating the osmotic resistance of erythrocytes fast and objectively, and can be used for differential diagnosis in hereditary spherocytosis.